2021
DOI: 10.3390/mi12091060
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Microfluidic Spiral Separation Device for Continuous, Pulsation-Free and Controllable CHO Cell Retention

Abstract: The development of continuous bioprocesses—which require cell retention systems in order to enable longer cultivation durations—is a primary focus in the field of modern process development. The flow environment of microfluidic systems enables the granular manipulation of particles (to allow for greater focusing in specific channel regions), which in turn facilitates the development of small continuous cell separation systems. However, previously published systems did not allow for separation control. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The device is fabricated from a biocompatible and heat-resistant 34 polyacrylate material by high-resolution 3D printinga technique that enables the manufacturing of microfluidic devices and has accordingly assumed increasing importance in many biotechnology-related fields, ranging from diagnostics to cell culture. [35][36][37][38][39] Compared to standard fabrication processes such as polydimethylsiloxane-based soft-lithography, 10,12,40 3D printing offers rapid prototyping of complex structures in a single step, 38,41 the use of various and versatile materials, 34,40,42 and does not require sophisticated microfabrication facilities. 12,38 The functionality of the GG is first established off-chip, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The device is fabricated from a biocompatible and heat-resistant 34 polyacrylate material by high-resolution 3D printinga technique that enables the manufacturing of microfluidic devices and has accordingly assumed increasing importance in many biotechnology-related fields, ranging from diagnostics to cell culture. [35][36][37][38][39] Compared to standard fabrication processes such as polydimethylsiloxane-based soft-lithography, 10,12,40 3D printing offers rapid prototyping of complex structures in a single step, 38,41 the use of various and versatile materials, 34,40,42 and does not require sophisticated microfabrication facilities. 12,38 The functionality of the GG is first established off-chip, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The geometrical configurations of microfluidic platforms can be very different (for example, channels, tanks, separators, mixers, etc. [ 57 , 58 ]) and depend on the application. If microfluidic devices are created only for detecting certain biological components, they usually have a simple geometric structure in the form of one or more channels with sizes from micrometers to millimeters in cross-section.…”
Section: Methods For Manufacturing Microfluidic Structures For Biosen...mentioning
confidence: 99%
“…For example, it is necessary to sort out certain components or particles to increase the concentration of the detected component. In this case, the geometry of the microfluidic system will be more complex and passive, or active separation structures can be added to the chip [ 57 , 58 ]. For labelled techniques, the microfluidic chip can be expanded with microfluidic mixers [ 59 ] to blend the material under test (MUT) with fluorescent components or nanoparticles.…”
Section: Methods For Manufacturing Microfluidic Structures For Biosen...mentioning
confidence: 99%
“…While 3D-printed inertial focusing devices for bioprocess applications are still rare, we believe that these tools will increasingly be employed for such operations in the future. For example, Enders et al have shown that these 3D-printed spiral cell separator devices can be used for cell retention to enable continuous cultivation processes [64]. Such systems could also potentially be used to concentrate cells with the aim to improve the transient transfection of mammalian cell lines used for protein production.…”
Section: Applications In Mammalian Cell Culturementioning
confidence: 99%